The Millennium Tower in Magdeburg - Grabert, Eike; Seredenkina, Svetlana (project baikal, 2004)
The Millenium Tower in Magdeburg, Germany, was built in 1999. It is possibly the biggest wooden tower of the world. The dissymetric «slanting» tower is 60 meters high, the foundation is 70 meters by 50 meters, and the size is 61000 cubic meters. The panelling is made of glass fabric. On the whole 5500 cubic meters of timber was used. On its 8030 square meters the tower houses a big exhibition about the history of mankind and scientific development.